An Internet of Things-based Air Pollution Detection System - Mat Saari, Nurul Aida; Kamaludin, Hazalila; Mohd Safa, Noor Zuraidin; Abd.Hamid, Isredza Rahmi (Journal of Soft Computing and Data Mining, 2022)
The Internet of Things (IoT)-based air pollution detection system using gas sensors is a system that is developed to detect air pollution using IoT technology. Air pollution is a condition where there is a mixture of harmful chemicals in the air we inhale that can cause damage to humans and the surroundings. The issue of polluted air nowadays has made people become more aware of the air quality they inhale. The system has been developed using MQ2 and MQ9 gas sensors to detect the air pollution level. The system involved two features in helping users read the air pollution level and notify the reading through a mobile app. Users also get notified of the reading through a pop-up notification. The mobile application development uses Android Studio, while Google Firebase is used as the database for the system. This IoT-based air pollution detection system is successfully developed and notified users about the air pollution reading to be more aware of their surroundings.